Handbook of mind-body medicine for primary care - Moss, Donald 1949-; Davies, Terence C.; McGrady, Angele; Wickramasekera, Ian (SAGE, 2003)
Emphasizing the concepts and technologies of clinical psychophysiology in providing an evidence-based empirical approach to problems of patients in primary care medicine, this text has a bio-psychosocial perspective